Analisis Struktur dan Nilai Budaya dalam Cerita Rakyat Sumatera Selatan - Anita Anita; Yessi Fitriani; Puspa Indah Utami (Departement of Mathematics Education, 2023)
Oral literature is always interesting to be the subject of scientific study. Folklore that has spread almost throughout the region of South Sumatra is still not much used as an object of serious research, even though it contains noble values that can be a guide in living life as individuals, social beings, and God's creatures. This study aims to determine the structure and cultural values of the folklore of South Sumatra. This research is a qualitative descriptive study using an objective approach that will present the data according to what was found. Based on the results of data analysis carried out on five folk tales originating from five districts/cities in South Sumatra, it was found that there were variations in themes, plots, characters, and settings in each story, as well as 32 cultural values in it which were divided into three forms of relationships, namely human relationship with himself, human relationship with the environment and human relationship with the Creator. These thirty-two values are still very relevant to the current situation